ECONOMIC VALUATION WITH TRAVEL COST METHOD (TCM) SLANIK WATERPARK SOUTH LAMPUNG DISTRICT - Muhammad Teguh Wibowo; Zainal Abidin; Lina Marlina (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
This study aims to analyze: (1) the factors that affecting the number of tourist visits, (2) the economic value of the Slanik Waterpark in South Lampung District, (3) the visitor satisfaction with tourism cost attribute. This study uses survey method involving 70 respondents. The first objective uses multiple linear regression analysis, the second objective uses consumer surplus analysis, and the third uses the Customer Satisfaction Index (CSI) analysis. Data was collected in June until July 2020. The research shows that the factors that influence the number of tourist visits Slanik Waterpark are travel costs and days of visits, the economic value of the Slanik Waterpark tourist attraction is Rp13,060,150,376 every year, the visitors are satisfied with the cost attributes incurred when traveled to Slanik Waterpark. Key words : tourism, economic value, visitor satisfaction